The chocolate shark shenanigans - Carl, JoAnna (Carl, JoAnna. Chocoholic mystery., 2019)
"When a house near Lee and Joe's home goes up for sale, the couple teams up with Lee's aunt and uncle, Nettie and Hogan, to buy it, remodel it, and resell it for a sweet profit. But after the owners of the house, the Baileys, accept their offer, a local developer, Richard "Spud" Dirk, suddenly swoops in with a higher one, and it seems their dreams might be snatched away. Lee, never as passionate about the plan as her husband and uncle, is anxious to get back to focusing on managing TenHuis Chocolade. But when a long-hidden gun is found behind a pipe in the Baileys' basement, she begins to suspect a mystery is afoot. And when Spud turns up dead in the Baileys' carport a few days later, it becomes clear there's something rotten at the foundation..."--